A Novel Peer-To-Peer Energy Sharing Business Model for the Portuguese Energy Market - Klein, Lurian Pires (2019)
The co-evolution of techno-economic, societal, environmental and political-institutional systems towards sustainable energy transitions is largely influencing the disruptive reconfiguration of the energy sector across the globe. At the heart of this disruption is the peer-to-peer energy sharing concept. Nonetheless, peer-to-peer energy sharing business models are yet very little put into practice due to the rigid energy market structures and lagging regulatory frameworks across the globe. In view of this, this paper presents a novel peer-to-peer energy sharing business model developed specifically for the context of the Portuguese energy market, which was successfully trialed in three pilot projects in Portugal under real market conditions. All things considered, the novelty of this paper lies on an innovative approach for the collaborative use of the surplus electricity generation from photovoltaic systems between end-users under the same low voltage/medium voltage transformer substation, which resulted in direct financial benefits to them. While absent deregulation obstructs the implementation of e ective peer-to-peer energy sharing markets in Portugal, such demonstration projects are essential to challenge restrictive regulatory frameworks that do not keep pace with techno-economic and societal innovations, thus helping to build the emerging consumer-centric energy regime and disrupt the old one.